1983
DOI: 10.1038/303081a0
|View full text |Cite
|
Sign up to set email alerts
|

Novel renin inhibitors containing the amino acid statine

Abstract: The proteolytic enzyme renin (EC3.4.99.19) cleaves the protein substrate angiotensinogen to yield angiotensin I, the decapeptide substrate transformed by converting enzyme into the pressor substance angiotensin II. Although the contribution of this pathway to the maintenance of normal blood pressure is unclear, it seems to be a major factor in various hypertensive states. Important progress in the control of hypertension has been achieved by development of the potent inhibitors SQ-14,225 (captopril) and MK-421… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(72 citation statements)
references
References 29 publications
0
72
0
Order By: Relevance
“…Pepstatin derivatives such as lactoyl-pepstatin have Ki values ranging from 4 x 10-10 to 6 x 10-6 M towards human pepsin and gastricsin respectively (Valler et al, 1985a). Similarly, synthetic peptide inhibitors of renin containing statine (Boger et al, 1983) or other non-hydrolysable analogues (Szelke et al, 1982;Hallett et al, 1985), although they do display very effective inhibition of human renin (Ki values approx. 10-9-010 M), nevertheless demonstrate weaker interactions (approx.…”
Section: Methodsmentioning
confidence: 99%
“…Pepstatin derivatives such as lactoyl-pepstatin have Ki values ranging from 4 x 10-10 to 6 x 10-6 M towards human pepsin and gastricsin respectively (Valler et al, 1985a). Similarly, synthetic peptide inhibitors of renin containing statine (Boger et al, 1983) or other non-hydrolysable analogues (Szelke et al, 1982;Hallett et al, 1985), although they do display very effective inhibition of human renin (Ki values approx. 10-9-010 M), nevertheless demonstrate weaker interactions (approx.…”
Section: Methodsmentioning
confidence: 99%
“…Kinetic studies with SRI indicated partial noncompetitive inhibition, with a K i value of 37.5 mM. The renin inhibitors reported to date are mainly peptides, pepstatin-and related compounds, 23,24) except for Aliskiren. 25) No-peptidic inhibitor, Aliskiren, is one of the most potent oral renin inhibitors.…”
Section: Isolation Of Soybean Renin Inhibitormentioning
confidence: 99%
“…Both C3 atoms of the statine residues are in the S-con®guration. Previous studies (Rich et al, 1980;Boger et al, 1983;Bailey et al, 1993) suggest that the 3S enantiomers of the statine residue at the P1±P1 H position are much more potent than the 3R enantiomers for pepstatin-type inhibitors. Our present study is consistent with these studies and suggests that RMP is also stereoselective in binding with pepstatin-type inhibitors.…”
Section: Binding Subsitesmentioning
confidence: 94%